Public ritual and the proclamation of Richard Cromwell in English towns, September 1658 - Calladine, Amy (Cambridge University press, 2017)
The requirement to proclaim Richard Cromwell lord protector in September 1658 forced town leaders to engage with an unstable political context through the production of a large-scale public event. This article examines the ceremonies used in a range of provincial towns to offer a new perspective on urban culture in 1650s England. By analyzing both contemporary print and the records of civic government, it reveals how urban inhabitants could maintain a variety of performative responses to state directive whilst approaching the moment of succession actively and pragmatically to confront issues specific to their respective locales. Crucially, there was no standard ritual experience and civic authorities remained relatively free to modify existing codes and apply them in the way/s that made most sense to their particular situation. In addition to confirming the essentially ambiguous nature of ceremonial expectation in this context, the findings presented in this article complicate our understanding of urban government during the last months of the protectorate by emphasizing the capacity for towns of varied religious and/or political complexion to use public ritual to further corporate interests and negotiate a range of specific concerns in a national and a local framework.